Comparison of Intrathecal Morphine and Fentanyl in Postoperative Pain Management of Spine Surgeries: A Randomized Double-blind Clinical Trial - Ehsan Parsa; Mehran Ilaghi; Hamed Reihani-Kermani (Iranian Journal of Neurosurgery)
Background and Aim: This study aims to compare the effectiveness of intrathecal morphine andfentanyl in reducing postoperative pain in patients undergoing spinal surgery.Methods and Materials/Patients: This was a randomized, double-blind clinical trial involving 80patients who were candidates for spinal surgery. The participants were randomly assigned totwo groups (n=40 each) and received either intrathecal morphine (0.2 mg) or fentanyl (25 µg). Postoperative pain was evaluated utilizing the visual analogue scale (VAS) at 4, 6, 12, and 18 h postsurgery. The time interval before a supplementary analgesic dose was required for pain control was recorded. Side effects, including pruritus, nausea/vomiting, and respiratory depression were monitored. Results: No significant differences were observed in age, sex, or operation type between the two groups. Patients in the morphine group exhibited remarkably lower VAS scores at all the assessed postoperative time points (P=0.001). Moreover, patients in the morphine group showed significantly lower overall mean VAS scores than those in the fentanyl group (3.75; 95% confidence interval [CI], 3.53%, 3.97% vs 5.06; 95% CI, 4.85%, 5.27%; P<0.001). The time to analgesic administration was significantly longer in the morphine group compared to the fentanyl group(P=0.001). The occurrence of postoperative nausea and vomiting was significantly higher in the morphine group (37.5%) than in the fentanyl group (15.0%, P=0.022). The incidence of pruritus did not differ significantly between the two groups. No cases of respiratory depression have been reported. Conclusion: Intrathecal morphine was more effective in reducing postoperative pain and prolonging the time to rescue analgesic administration compared to intrathecal fentanyl in patients undergoing spine surgeries. However, a higher incidence of postoperative nausea/vomiting should be considered.